Did Britain have a ‘Keynesian revolution’? (2007)
The common understanding of the phrase, ‘the Keynesian revolution’, is a reappraisal of the theory of fiscal policy after the publication of Keynes’s The General Theory of Employment, Interest and Money in 1936, followed by the practical adoption of the new ideas by the major industrial countries in the 1940s and 1950s. Specifically, whereas before the Keynesian revolution governments’ priority in fiscal policy was to maintain a balanced budget, afterwards the budgetary balance was varied contra-cyclically in order to reduce fluctuations in economic activity. Britain is often regarded as the home of the Keynesian revolution. For example, the opening sentence of chapter VII of Christopher Dow’s The Management of the British Economy 1945–60 asserts, ‘There is probably no country in the world that has made a fuller use than the UK of budgetary policy as a means of stabilizing the economy.’1 The characterization of British macroeconomic policy as ‘Keynesian’ in the immediate post-war decades has become routine and unchallenged in standard textbooks.